Dynamics of microbial communities, texture and flavor in Suan zuo yu during fermentation. (1st December 2020) - Wang, Zehan; Xu, Zhe; Sun, Liming; Dong, Liang; Wang, Zhenyu; Du, Ming
Graphical abstract: Highlights: Dominated microbial community of Suan zuo yu was firstly clarified. Free amino acid composition and the taste active amino acids were compared. Flavor compounds and key odorant of Suan zuo yu were identified. Abstract: Suan zuo yu is a traditional Chinese fermented product. We explored the microbial diversity, the dynamic changes of texture and flavor compounds at different fermentation times (up to 24 d). Results showed that Weissella and Lactobacillus may play a vital role in fermentation especially for the flavor. At the end of fermentation, the taste activity value of Asp, Glu, and His were 21.61, 17.29 and 7.73, respectively. The bound water increased gradually indicated by low-field nuclear magnetic resonance, and the hardness was also increased. During the whole fermentation process, the myosin heavy chain protein and actin decreased obviously. Gas chromatography-mass spectrometry showed that a total of 80 volatile compounds were detected, and 6 alcohols, 6 aldehydes and 6 esters increased significantly, which mainly contributed to the flavor of Suan zuo yu . This study provides a theoretical basis for the industrial production of fermented fish.